Modeling and Using Context 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011. Proceedings - Beigl, Michael; Christiansen, Henning; Roth-Berghofer, Thomas R.; Kofod-Petersen, Anders; Coventry, Kenny R.; Schmidtke, Hedda R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 7th International and Interdisciplinary Conference on Modeling and Using Context, CONTEXT 2011, held in Karlsruhe, Germany in September 2011. The 17 full papers and 7 short papers presented were carefully reviewed and selected from 54 submissions. In addition the book contains two keynote speeches and 8 poster papers. They cover cutting-edge results from the wide range of disciplines concerned with context, including the cognitive sciences (linguistics, psychology, philosophy, computer science, neuroscience), the social sciences and organization sciences, and all application areas.
Keywords: Computer science; Artificial intelligence; Social sciences -- Data processing; Information systems; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Information Systems Applications (incl. Internet).; Computer Appl. in Social and Behavioral Sciences; Computer Appl. in Arts and Humanities; History of Computing